2019
DOI: 10.1002/1873-3468.13661
|View full text |Cite
|
Sign up to set email alerts
|

The activation mechanism of plant S6 kinase (S6K), a substrate of TOR kinase, is different from that of mammalian S6K

Abstract: The S6 kinases (S6Ks) are known to be activated by the target of rapamycin through phosphorylation of their hydrophobic motif (HM). However, our previous research showed that the HM site of plant S6Ks is not phosphorylated and is not essential for their activity in yeast cells lacking Ypk3, an ortholog of mammalian S6K. Here, we demonstrate that the HM site of mammalian S6Ks is phosphorylated and is indispensable for their activity in yeast ypk3∆ cells. Furthermore, pseudo‐phosphorylation at the HM site of pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…S6Ks proteins are another target downstream of the mTOR pathway that are encoded by two cellular genes: S6K1 and S6K2 [63]. Many studies have shown that S6K1 can affect cell growth and proliferation by promoting the translation of related mRNAs.…”
Section: Akt Target Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…S6Ks proteins are another target downstream of the mTOR pathway that are encoded by two cellular genes: S6K1 and S6K2 [63]. Many studies have shown that S6K1 can affect cell growth and proliferation by promoting the translation of related mRNAs.…”
Section: Akt Target Proteinsmentioning
confidence: 99%
“…S6K1 can directly phosphorylate relevant components and factors associated with translation mechanism, such as ribosomal protein S6, eIF4B and PDCD4 [64]. Studies have shown that mTORC1 can activate SREBP1 through S6K1 [63]. Furthermore, overactivation of mTOR enhances lipid anabolism in mouse models of obesity and diabetes.…”
Section: Akt Target Proteinsmentioning
confidence: 99%
“…In addition, mTORC1 complex assembly is facilitated by a scaffolding protein Raptor, whose suppression is relieved by AKT-mediated phosphorylation of PRAS40 [140][141][142] (Figure 5). Broadly, mTORC1 is involved in processes of enhanced protein synthesis and growth through downstream effectors like S6 kinase; lipid synthesis through sterol responsive element binding protein (SRBEP); cellular stress responses through its negative regulator AMPK; and cell survival through autophagy and ubiquitin proteosome regulation [143][144][145][146]. In neuronal context, mTORC1 is activated through stimuli like brain-derived neurotrophic factor (BDNF), reelin, glutamate, gamma-aminobutyric acid (GABA), acetyl choline, and neuropeptides [147][148][149].…”
Section: Akt and Mtor Pathwaymentioning
confidence: 99%
“…S6Ks are members of the AGC family (which includes PKA, PKG and PKC) and are conserved substrates of TOR signaling [ 8 , 9 ]. Both animals and plants have two members of S6Ks, which are S6K1 and S6K2 [ 9 , 10 ]. TOR phosphorylates p70kDa ribosomal S6 kinase (S6K)-1 in Thr-389 residue and Thr-449 residue in animals and plants, respectively [ 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The activation of mammalian S6K requires phosphorylation at three conserved sites, namely the T-loop, the TM site and the HM site, which show high homology to plant S6Ks, except that the four proline residues directing Ser/Thr sites in the C-terminal domain are absent in plants. In contrast, plant S6Ks can be activated by phosphorylation at two of these three sites [ 10 ].…”
Section: Introductionmentioning
confidence: 99%